2014
DOI: 10.7448/ias.17.1.19064
|View full text |Cite
|
Sign up to set email alerts
|

Re‐testing and misclassification of HIV‐2 and HIV‐1&2 dually reactive patients among the HIV‐2 cohort of The West African Database to evaluate AIDS collaboration

Abstract: IntroductionWest Africa is characterized by the circulation of HIV-1 and HIV-2. The laboratory diagnosis of these two infections as well as the choice of a first-line antiretroviral therapy (ART) is challenging, considering the limited access to second-line regimens. This study aimed at confirming the classification of HIV-2 and HIV-1&2 dually reactive patients followed up in the HIV-2 cohort of the West African Database to evaluate AIDS collaboration.MethodA cross-sectional survey was conducted from March to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
4
26
0
2
Order By: Relevance
“…Thus, with a low rate of transmission, compare to HIV-1, HIV-2 infects old people aged more than 40 years old [17] [24]. This finding was confirmed in our study where the mean age was 43.5 years and 65.0% of HIV-2 infected patients were at least 40 years old.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, with a low rate of transmission, compare to HIV-1, HIV-2 infects old people aged more than 40 years old [17] [24]. This finding was confirmed in our study where the mean age was 43.5 years and 65.0% of HIV-2 infected patients were at least 40 years old.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported using a suboptimal testing strategy that differed from the WHO recommendations [5,8,1114,16,2230,3234,36–39,4244,49,51,53,59,62,64–66,68,72,75]. Suboptimal testing strategies included using a highly specific first-line test and highly sensitive second-line test [14,33,39,55], using a single RDT for HIV-positive diagnoses [11,66,72], using a high prevalence testing strategy in a low prevalence setting [16,49], using a parallel testing algorithms and a tiebreaker testing strategy (where a third assay is used to resolve discrepant test results and rule in HIV infection) [5,12,13,16,24,25,2730,32,34,36,37,68].…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of dual HIV infection remains difficult without the measurement of both viruses by PCR and the appropriate detection algorithms when using a serological testing Tchounga et al 2014. Immunological and virological follow-up of both HIV-1 and HIV-2 in dually seropositive patients is recommended.…”
Section: Resultsmentioning
confidence: 98%